High ATF4 Expression Is Associated With Poor Prognosis, Amino Acid Metabolism, and Autophagy in Gastric Cancer - Wang, Mingliang; Lu, Yida; Wang, Huizhen; Wu, Youliang; Xu, Xin; Li, Yongxiang (Frontiers in Oncology, 2021)
Abstract Background: The roles of ATF4 underlying GC remain unclear. The purpose of this study was to investigate the expression levels and biological functions of ATF4 in GC. Methods: Expression of ATF4 was detected by qPCR, western blotting and immunohistochemistry. Cox regression was used for survival analysis and the construction of the nomogram. Immunofluorescence was used to identify the intracellular localization of ATF4. Knockdown and overexpression of ATF4 in GC cells followed by wound-healing, Transwell assay, EdU staining, Calcein AM/Propidium Iodide staining and cell cycle detection were used to examine its function in vitro. Transmission electron microscopy was performed to assess the autophagy levels upon ATF4 silencing. KEGG analysis and GSEA were used to determine gene enrichment. SPSS 22.0 software, GraphPad Prism 7.0 and R version 3.6.1 were used for statistical analysis. Results: ATF4 expression was upregulated in GC cells and tissues compared with corresponding normal tissues. Survival analysis suggested that high ATF4 expression was strongly associated with worse overall survival of GC patients (P<0.001). Nomogram and ROC curves demonstrated that ATF4 was a highly sensitive and specific prognostic marker of GC (C-index=0.797, AUC of 3-year OS=0.855, and AUC of 5-year OS=0.863). In addition, ATF4 knockdown inhibited cell proliferation, migration, invasion and cell cycle progression of GC cells in vitro, while overexpression of ATF4 exerted opposite effects. Bioinformatic analysis showed that ATF4 could promote GC progression possibly by regulating Asn metabolism and autophagy pathways. Further experiments indicated that ATF4 expression was significantly positively correlated with ASNS expression. The inhibition of cell clone formation in Asn-deprived conditions was more significant in the shATF4 group. Finally, we found that ATF4 promoted autophagy though regulating the mTORC1 pathway in GC cells. Conclusion: These findings suggested that ATF4 can significantly promote GC development and serves as an independent prognostic factor for GC.